Prevalence of Mandibular Retromolar Canal on Cone Beam Computed Tomography Scan - Kamal Amini; Roshanak Ghafari; Shadi Kazemi; Fatemeh Bagheri (Islamic Dental Association of Iran, 2015)
Background and Aim: The retromolar canal is an anatomical structure in the mandible and a type of bifid inferior alveolar canal. The retromolar canal may provide accessory innervation to the mandibular molars or contain an aberrant buccal nerve; thus, this canal is of clinical significance. The aim of this study was to evaluate the prevalence of retromolar canal on cone-beam computed tomography (CBCT) scans. Materials and Methods: In this descriptive-analytical study, 151 inferior alveolar canals in 102 patients (102 unilateral and 49 bilateral) with third molar teeth requiring CBCT scans were evaluated. The scans were evaluated for presence of the retromolar canal and linear measurements (distance to second molar, height and width) were made. The data were analyzed paired t-test and chi square test. Results: The prevalence of retromolar canal was 7.3% (n=11). With regard to linear measurements, the mean distance from the retromolar canal to the second molar was 12.76± 4.3mm. The mean height of the canal was 6.66 ±2.18mm, and the mean width was 1.7± 0.6mm. The presence of retromolar canal was not statistically correlated with sex, side of the jaw or age (p=0.146). Conclusion: The prevalence of retromolar canal on CBCT scans was 7.3%.